Mortality risk in European children with end-stage renal disease on dialysis - Chesnaye, Nicholas; Schaefer, Franz; Groothoff, Jaap W.; Bonthuis, Marjolein; Reusz, György; Heaf, James G.; Lewis, Malcolm; Maurer, Elisabeth; Paripović, Dušan; Zagozdzon, Ilona; van Stralen, Karlijn J.; Jager, Kitty J. (Kidney international, 2016)
We aimed to describe survival in European pediatric dialysis patients and compare the differential mortality risk between patients starting on hemodialysis (HD) and peritoneal dialysis (PD). Data for 6473 patients under 19 years of age or younger were extracted from the European Society of Pediatric Nephrology, the European Renal Association, and European Dialysis and Transplant Association Registry for 36 countries for the years 2000 through 2013. Hazard ratios (HRs) were adjusted for age at start of dialysis, sex, primary renal disease, and country. A secondary analysis was performed on a propensity score-matched (PSM) cohort. The overall 5-year survival rate in European children starting on dialysis was 89.5% (95% confidence interval [CI] 87.7%-91.0%). The mortality rate was 28.0 deaths per 1000 patient years overall. This was highest (36.0/1000) during the first year of dialysis and in the 0- to 5-year age group (49.4/1000). Cardiovascular events (18.3%) and infections (17.0%) were the main causes of death. Children selected to start on HD had an increased mortality risk compared with those on PD (adjusted HR 1.39, 95% CI 1.06-1.82, PSM HR 1.46, 95% CI 1.06-2.00), especially during the first year of dialysis (HD/PD adjusted HR 1.70, 95% CI 1.22-2.38, PSM HR 1.79, 95% CI 1.20-2.66), when starting at older than 5 years of age (HD/PD: adjusted HR 1.58, 95% CI 1.03-2.43, PSM HR 1.87, 95% CI 1.17-2.98) and when children have been seen by a nephrologist for only a short time before starting dialysis (HD/PD adjusted HR 6.55, 95% CI 2.35-18.28, PSM HR 2.93, 95% CI 1.04-8.23). Because unmeasured case-mix differences and selection bias may explain the higher mortality risk in the HD population, these results should be interpreted with caution.
Gesehen am 30.04.2020